fiqih pendekatan komparatif - Firli, Dania (FIHROS: Jurnal Sejarah dan Budaya, 2022)
Today,there are peoplewho study religion by discussing the past year compared to god according to other religions.there are those who study islam by reading the koran and then compare it with the holy books of other religions.there are those who study the life of Muhammad saw then compared to the prophets of religions.all of these are examples of religious studies using a comparative approach.recently,Islamic studies have been accused of being unproductive studies,just repetition,not pragmatic,only paying for theories that cannot be appliet to everday life and have no steps.clear methodology.it is not an exaggeration to say that theIslamic study model in the west has had a major influence in raising  awareness of the importance of methodological instruments among scholars who have not come from orhave not tasted education in the west.one of the approaches introduced by western scholars is this comparative approach the non muslim reviewers.